Clinical Finding of Electroencephalographic (EEG) Data in Adults: A Retrospective study (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Electroencephalography (EEG) is the first and only real-time monitor of epileptic seizures, and is a powerful measure of cerebral function in the seriously ill.Objective: The purpose of this study was to see the common conditions for doing EEG.Methods: This study was performed retrospectively by collecting and reviewing the electro-clinical information of the adult patients to whom EEGs were done at the 'Central Hospital' laboratory. Clinical problems were categorized into seizures, fainting attacks, headache, giddiness, vertigo, stroke, suicidal tendency, sudden aggressiveness and head injury. Routine EEGs were performed for 30 minutes. EEG findings were categorized as normal for the age, localized or generalized epileptiform discharges, non-epileptogenic dysfunction.Result: In total 53 adult patients 34% population had fainting attacks, 28% had seizures, 10% had stroke and 28% had complaint related to behavior, suicidal tendency, headache and post head injury problems. EEG was normal in 60%.Conclusion: EEG is advised for diverse conditions. The proportion of epileptic patients is small, although this is the principal indication for doing routine EEG.J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 14-17